PENURUNAN KUALITAS AIR BATANG AYUMI KOTA PANGSIDIMPUAN - Fatma Suryani Harahap; Laila Tussifah Lubis (Eksakta : Jurnal Penelitian dan Pembelajaran MIPA, 2020)
The discharge of leachate increasingly exacerbates the condition of the batang ayumi increasingly polluted due to a large amount of garbage and the pollution from TPA Batu bola Padangsidimpuan City. This study aims to analyze the water quality of Batang Ayumi. This study uses a descriptive exploratory method by surveying in advance to observe the environmental conditions of Batu Bola landfill as a consideration for the impact of Batu Bola landfill on the surrounding environment. Water quality measurements carried out at four sampling stations. At each station, two repetitions carried out. Parameters measured and observed were parameters of temperature, pH, DO, COD, BOD, and Turbidity. The results showed that the turbidity value of the Batang Ayumi at station II had exceeded the standard threshold; the quality is 4,7 NTU. In contrast, results of the data analysis of the Batang Ayumi river, it was concluded that the BOD concentration along with the Batang Ayumi, The value of BOD Ayumi Batang river water concentration is between 3.6 mg / l -3.9 mg / l.